Postsynthetic Improvement of the Physical Properties in a Metal–Organic Framework through a Single Crystal to Single Crystal Transmetallation1. (14th April 2015) - Grancha, Thais; Ferrando‐Soria, Jesús; Zhou, Hong‐Cai; Gascon, Jorge; Seoane, Beatriz; Pasán, Jorge; Fabelo, Oscar; Julve, Miguel; Pardo, Emilio
Abstract A single crystal to single crystal transmetallation process takes place in the three‐dimensional (3D) metal–organic framework (MOF) of formula MgII2MgII4[CuII2(Me3mpba)2]3⋅45 H2O (1; Me3mpba4−=N, N′‐2, 4, 6‐trimethyl‐1, 3‐phenylenebis(oxamate)). After complete replacement of the MgII ions within the coordination network and those hosted in the channels by either CoII or NiII ions, 1 is transmetallated to yield two novel MOFs of formulae Co2IICoII4[CuII2(Me3mpba)2]3⋅56 H2O (2) and Ni2IINiII4[CuII2(Me3mpba)2]3⋅ 54 H2O (3). This unique postsynthetic metal substitution affords materials with higher structural stability leading to enhanced gas sorption and magnetic properties.